2005
DOI: 10.3201/eid1101.040434
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Transmission on Cruise Ship

Abstract: We documented transmission by food and person-to-person contact; persistence of virus despite sanitization onboard, including introductions of new strains; and seeding of an outbreak on land.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
101
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 13 publications
(16 reference statements)
0
101
1
3
Order By: Relevance
“…Thirteen of these were subsequently excluded because they did not meet the inclusion criteria: five because they were reports of outbreaks on military ships, and eight because data about the location and the characteristics of the outbreak were not available. Twenty-two articles (Morillo et al 2012;Wikswo et al 2011;Vivancos et al 2010;Xerry et al 2009;Boxman et al 2009;Xerry et al 2008;Chimonas et al 2008;Verhoef et al 2008a, b;Takkinen 2006;Koopmans et al 2006;Ferson and Ressler 2005;Isakbaeva et al 2005;Widdowson et al 2004;Gallimore et al 2003;CDC 2002;Minooee and Rickman 1999;McEvoy et al 1996;Koo et al 1996;Herwaldt et al 1994;Khan et al 1994) met the inclusion criteria and were thus included in our review.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of these were subsequently excluded because they did not meet the inclusion criteria: five because they were reports of outbreaks on military ships, and eight because data about the location and the characteristics of the outbreak were not available. Twenty-two articles (Morillo et al 2012;Wikswo et al 2011;Vivancos et al 2010;Xerry et al 2009;Boxman et al 2009;Xerry et al 2008;Chimonas et al 2008;Verhoef et al 2008a, b;Takkinen 2006;Koopmans et al 2006;Ferson and Ressler 2005;Isakbaeva et al 2005;Widdowson et al 2004;Gallimore et al 2003;CDC 2002;Minooee and Rickman 1999;McEvoy et al 1996;Koo et al 1996;Herwaldt et al 1994;Khan et al 1994) met the inclusion criteria and were thus included in our review.…”
Section: Resultsmentioning
confidence: 99%
“…This estimate explains why the number of new cases per day continued to increase and why norovirus infection spread to new camps, even after implementation of enhanced hygiene measures. It is tempting to speculate that our fi ndings could be extrapolated to other hygiene measures to explain the typical pattern in several subsequent norovirus outbreaks on cruise ships and in hotels (9,26,27). The estimation procedure for the time course of the reproduction number has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested that norovirus outbreaks could be contained by rapid implementation of enhanced hygiene measures, such as washing hands, thoroughly cleaning contaminated surfaces, avoiding contact between sick and healthy persons, and requesting caretakers and cleaning staff to wear gloves and aprons (13)(14)(15)(16). However, in nursing homes or on cruise ships, norovirus can cause consecutive outbreaks, even after implementation of strict hygiene protocols (9,17,18). No quantitative estimates exist of the results of such enhanced hygiene measures on reducing further transmission of norovirus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This particularly refers to crewmembers, who are often four per cabins and therefore are more likely to become infected. In the present study, the prevalence of gastroenteritis complaints, which is mainly driven by norovirus [19,22,23], was low. According to the navigation area, the ship is subject to strict health inspections requiring the physician to notify all gastrointestinal infection and to respect cleaning protocols in case of outbreak.…”
Section: Discussionmentioning
confidence: 97%